Isoform‐specific effects of transforming growth factor β on endothelial‐to‐mesenchymal transition. Issue 11 (1st June 2018) - Sabbineni, Harika; Verma , Arti; Somanath, Payaningal R.
Abstract : Endothelial‐to‐mesenchymal transition (EndMT) was first reported in the embryogenesis. Recent studies show that EndMT also occurs in the disease progression of atherosclerosis, cardiac and pulmonary fibrosis, pulmonary hypertension, diabetic nephropathy, and cancer. Although transforming growth factor β (TGFβ) is crucial for EndMT, it is not clear which isoform elicits a predominant effect. The current study aims to directly compare the dose‐dependent effects of TGFβ1, TGFβ2, and TGFβ3 on EndMT and characterize the underlying mechanisms. In our results, all three TGFβ isoforms induced EndMT in human microvascular endothelial cells after 72 hr, as evidenced by the increased expression of mesenchymal markers N‐cadherin and α‐smooth muscle actin as well as the decreased expression of endothelial nitric oxide synthase. Interestingly, the effect of TGFβ2 was the most pronounced. At 1 ng/ml, only TGFβ2 treatment resulted in significantly increased phosphorylation (activation) of Smad2/3 and p38‐MAPK and increased expression of mesenchymal transcription factors Snail and FoxC2. Intriguingly, we observed that treatment with 1 ng/ml TGFβ1 and TGFβ3, but not TGFβ2, resulted in an increased expression of TGFβ2, thus indicating that EndMT with TGFβ1 and TGFβ3 treatments was due to the secondary effects through TGFβ2 secretion. Furthermore, silencing TGFβ2 using small interfering RNA blunted the expression of EndMT markers in TGFβ1‐ and TGFβ3‐treated cells. Together, our results indicate that TGFβ2 is the most potent inducer of EndMT and that TGFβ1‐ and TGFβ3‐induced EndMT necessitates a paracrine loop involving TGFβ2. Abstract : Our study demonstrates that transforming growth factor β2 (TGFβ2) is the most potent inducer of endothelial‐to‐mesenchymal transition (EndMT) and that TGFβ1‐ and TGFβ3‐induced EndMT necessitates a paracrine loop involving TGFβ2. Silencing TGFβ2 using small interfering RNA blunted the expression of EndMT markers in TGFβ1‐ and TGFβ3‐treated cells.